A qualitative assessment of community perceptions and practices towards schistosomiasis prior to introduction of a potential novel treatment option for preschool-age children in Kenya - Masaku, Janet; Gachohi, John M.; Sinkeet, Alice; Maghanga, Mary; Wakesho, Florence; Omondi, Wyckliff; Reigl, Lisa Sophie; Lange, Isabelle L.; Winkler, Andrea S.; Njenga, Sammy M.; Amuyunzu-Nyamongo, Mary (Frontiers in Tropical Diseases, 2024)
BackgroundOver 50 million preschool-age children (PSAC) in Africa need treatment for schistosomiasis but are excluded due to lack of a suitable child-friendly medication. The Paediatric Praziquantel Consortium has developed a novel paediatric formulation for PSAC. In advance of its roll-out, we conducted a social science study to draw lessons to inform implementation.MethodsWe conducted a cross-sectional study in eight villages in two purposively selected highly endemic Kenyan counties (Homa Bay and Kwale). We conducted 17 in-depth interviews with community opinion leaders and 21 with parents/guardians of PSAC. Twelve focus group discussions with parents/guardians of PSAC were also held. The aim was to assess their knowledge, perceptions, practices and willingness to participate in the medication’s roll-out for schistosomiasis. Thematic data analysis was performed.ResultsMost participants had heard of schistosomiasis and perceived it to be a serious disease whose treatment should be prioritised. Others felt it was a common disease that should not cause concern. Some people believed schistosomiasis was caused by witchcraft while others regarded it as a sexually transmitted infection. In addition, some practices like poor human waste disposal and water contact were thought to contribute to continued transmission of the disease.ConclusionCommunity members know and perceive schistosomiasis to be serious, but misinformation about its cause is prevalent. The study suggests the need for increased awareness creation to change the perceptions of communities in relation to schistosomiasis prevention and control. Community sensitisation should be prioritised in advance of medication roll-out.